Lithium-ion battery, positive electrode sheet and power-consuming device
By reasonably controlling the hydrogenation ratio of hydrogenated nitrile rubber and the carbon cladding of lithium iron phosphate in lithium-ion batteries, the problem of high diaphragm resistance is solved, and the efficiency and circulation performance of the battery are improved.
Patent Information
- Application Number
- CN202411195953.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-29
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-08-29
AI Technical Summary
Among the existing lithium-ion batteries, lithium iron phosphate is a battery system with positive electrode active material, and the diaphragm resistance is high, which affects the energy density, circulation performance and safety performance of the battery.
By reasonably controlling the hydrogenation ratio of hydrogenated nitrile rubber to 30%~85%, and combining the surface carbon coating of lithium iron phosphate, the components of the positive electrode active layer are optimized to reduce the diaphragm resistance.
Lower diaphragm resistance is achieved, the first-time Coulomb efficiency of lithium-ion batteries is improved, and the optimal circulation capacity is maintained under high temperature conditions.
Smart Images

Figure CN118738285B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of secondary batteries, and in particular to a lithium-ion battery, a positive electrode sheet and an electrical device. Background Art
[0002] The statements herein merely provide background information related to the present application and do not necessarily constitute prior art.
[0003] In recent years, the application scope of secondary batteries such as lithium-ion batteries has become increasingly wide, and they have been widely used in energy storage power systems such as hydropower, thermal power, wind power and solar power stations, as well as power tools, electric bicycles, electric motorcycles, electric vehicles and other fields. As lithium-ion batteries have made great progress, higher requirements have been put forward for their energy density, cycle performance and safety performance.
[0004] For battery systems using lithium iron phosphate as the positive electrode active material, hydrogenated nitrile rubber is usually used as a dispersant to improve the dispersibility of the slurry, thereby reducing the membrane resistance. However, the slurry dispersibility of such battery systems needs to be further improved. Summary of the invention
[0005] In order to achieve the above-mentioned objectives, the present application provides a lithium-ion battery with low membrane resistance, a positive electrode plate, and an electrical device including the lithium-ion battery and the positive electrode plate.
[0006] In a first aspect of the present application, a lithium ion battery is provided, comprising a positive electrode plate, wherein the positive electrode plate comprises a positive electrode active layer, wherein the components of the positive electrode active layer comprise a positive electrode active material and an additive, wherein the positive electrode active material comprises lithium iron phosphate, and the additive comprises hydrogenated nitrile rubber, wherein the hydrogenation ratio of the hydrogenated nitrile rubber is 30% to 85%;
[0007] The meaning of the hydrogenation ratio is: the molar content of double bonds in the nitrile rubber is P1, and the molar content of double bonds in the hydrogenated nitrile rubber obtained after the corresponding hydrogenation is P2, then the hydrogenation ratio is (P1-P2) / P1.
[0008] The above lithium-ion battery reasonably controls the hydrogenation ratio of hydrogenated nitrile rubber to 30%~85%, which can obtain lower membrane resistance.
[0009] In some embodiments, the hydrogenation ratio of the hydrogenated nitrile rubber is 55% to 70%.
[0010] In some embodiments, the hydrogenated nitrile rubber has at least one of the following characteristics (1) to (2):
[0011] (1) Weight average molecular weight is 500~1000000;
[0012] (2) The molar proportion of acrylonitrile structural units is 5%~30%.
[0013] In some embodiments, the hydrogenated nitrile rubber has at least one of the following characteristics (1) to (2):
[0014] (1) Weight average molecular weight is 1000~100000;
[0015] (2) The molar proportion of acrylonitrile structural units is 10%~20%.
[0016] Furthermore, reasonable control of the weight-average molecular weight of the hydrogenated nitrile rubber and the molar ratio of the acrylonitrile structural unit can further improve the dispersion stability of the slurry, reduce the membrane resistance, and improve the initial coulombic efficiency of the lithium-ion battery, while also being able to obtain a better high-temperature cycle capacity retention rate.
[0017] In some embodiments, in the positive electrode active layer, the mass percentage of the hydrogenated nitrile rubber is 0.1% to 1%.
[0018] In some embodiments, the surface of the lithium iron phosphate has a carbon coating layer. The carbon coating layer on the surface of the lithium iron phosphate usually has residues such as -OH and -COOH, which can form hydrogen bonds with the cyanide groups in the hydrogenated nitrile rubber to improve the dispersion effect of the slurry.
[0019] In some embodiments, the graphitization degree of the carbon coating layer is 10% to 30%.
[0020] In a second aspect of the present application, a positive electrode plate is provided, the positive electrode plate comprising a positive electrode active layer, the components of the positive electrode active layer comprising a positive electrode active material and an additive, the additive comprising hydrogenated nitrile rubber, and the hydrogenation ratio of the hydrogenated nitrile rubber is 30% to 85%;
[0021] The meaning of the hydrogenation ratio is: the molar content of double bonds in the nitrile rubber is P1, and the molar content of double bonds in the hydrogenated nitrile rubber obtained after the corresponding hydrogenation is P2, then the hydrogenation ratio is (P1-P2) / P1.
[0022] In some embodiments, the positive electrode plate is the positive electrode plate in the lithium-ion battery as described above.
[0023] A third aspect of the present application provides an electrical device comprising at least one of the lithium-ion battery described above and the positive electrode sheet described above. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to better describe and illustrate the embodiments or examples provided by the present application, reference may be made to one or more drawings. The additional details or examples used to describe the drawings should not be considered as limiting the scope of the disclosed application, the embodiments or examples currently described, and any of the best modes of these applications currently understood. Moreover, the same reference numerals are used throughout the drawings to represent the same components. In the drawings:
[0025] Figure 1 FIG. 1 is a schematic diagram of a lithium-ion battery according to an embodiment of the present application.
[0026] Figure 2 for Figure 1 An exploded view of a lithium-ion battery according to an embodiment of the present application is shown.
[0027] Description of reference numerals:
[0028] 1. lithium-ion battery; 11. housing; 12. electrode assembly; 13. cover plate. DETAILED DESCRIPTION
[0029] In order to facilitate the understanding of the present application, the present application will be described more fully below with reference to the relevant drawings. The preferred embodiments of the present application are given in the drawings. However, the present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present application more thorough and comprehensive.
[0030] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application. The term "and / or" used herein includes any and all combinations of one or more of the related listed items.
[0031] The "range" disclosed in the present application can be limited in the form of a lower limit and an upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The range limited in this way can be including or excluding end values, and any end value can be included or not included independently, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range. For example, if a range of 60 to 120 and 80 to 110 is listed for a specific parameter, it is understood that the range of 60 to 110 and 80 to 120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are also listed, the following ranges can all be expected: 1 to 3, 1 to 4, 1 to 5, 2 to 3, 2 to 4 and 2 to 5. In the present application, unless otherwise specified, the numerical range "a to b" represents the abbreviation of any real number combination between a and b, wherein a and b are both real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to listing the parameter as, for example, integers 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc. For example, when a parameter is expressed as an integer selected from "2-10", it is equivalent to listing the integers 2, 3, 4, 5, 6, 7, 8, 9 and 10.
[0032] In the present application, "plurality", "multiple" and the like, unless otherwise specified, refer to a number greater than or equal to 2. For example, "one or more" means one or greater than or equal to two.
[0033] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0034] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment or implementation of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments. The "implementation methods" mentioned herein have a similar understanding.
[0035] Those skilled in the art will appreciate that, in the methods of each embodiment or example, the order in which each step is written does not mean a strict order of execution and does not constitute any limitation on the implementation process, and the detailed order of execution of each step should be determined by its function and possible internal logic. If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or steps (b) and (a) performed sequentially. For example, the method may also include step (c), indicating that step (c) can be added to the method in any order, for example, the method may include steps (a), (b) and (c), or steps (a), (c) and (b), or steps (c), (a) and (b), etc.
[0036] In this application, in the open technical features or technical solutions described by the words "contain", "include", "include", etc., if there is no other explanation, additional members other than the listed members are not excluded, and it can be regarded as providing both closed features or solutions consisting of the listed members and open features or solutions including additional members in addition to the listed members. For example, A includes a1, a2 and a3. If there is no other explanation, it may also include other members or may not include additional members. It can be regarded as providing both the feature or solution of "A consists of a1, a2 and a3" and the feature or solution of "A includes not only a1, a2 and a3, but also other members".
[0037] In the present application, unless otherwise specified, A (such as B) means that B is a non-limiting example of A, and it can be understood that A is not limited to B. Some embodiments of the present application provide a lithium-ion battery, including a positive electrode plate, the positive electrode plate including a positive electrode active layer, the components of the positive electrode active layer including a positive electrode active material and an additive, the positive electrode active material including lithium iron phosphate, the additive including hydrogenated nitrile rubber, and the hydrogenation ratio of the hydrogenated nitrile rubber is 30% to 85%.
[0038] The above-mentioned lithium-ion battery reasonably controls the hydrogenation ratio of hydrogenated nitrile rubber to 30%~85%. When the hydrogenation ratio is greater than 85%, the double bond content in the hydrogenated nitrile rubber is too small, and the overall regularity of the molecule is relatively high, which is not conducive to cross-linking to form a cross-linked structure with large steric hindrance, thereby reducing the dispersibility and stability of the slurry, resulting in a higher membrane resistance; when the hydrogenation ratio is less than 30%, the double bond content in the hydrogenated nitrile rubber is too much, and its own excessive cross-linking reduces the dispersibility to lithium iron phosphate, which also reduces the dispersibility and stability of the slurry, resulting in a higher membrane resistance. Therefore, by reasonably controlling the hydrogenation ratio of hydrogenated nitrile rubber in the lithium iron phosphate battery system to 30%~85%, a lower membrane resistance can be obtained. Furthermore, the reduction in membrane resistance can also improve the first coulomb efficiency of lithium-ion batteries.
[0039] In other embodiments of the present application, the hydrogenation ratio of hydrogenated nitrile rubber of 30% to 85% can also enable the lithium ion battery to obtain better thermal stability and have a better cycle capacity retention rate under high temperature conditions. When the hydrogenation ratio is less than 30%, the double bond content in the hydrogenated nitrile rubber is too much, and thermal decomposition is easily caused, so that the heat resistance is significantly reduced, thereby affecting the cycle capacity retention rate of the lithium ion battery. When the hydrogenation ratio is greater than 85%, the double bond content in the hydrogenated nitrile rubber is too little, so that the cross-linking ratio is low, and the adhesion between the materials decreases significantly under high temperature conditions, which also causes the cycle capacity retention rate of the battery to decrease.
[0040] It can be understood that the "hydrogenation ratio" means that the molar content of double bonds in the nitrile rubber is P1, and the molar content of double bonds in the hydrogenated nitrile rubber obtained after the corresponding hydrogenation is P2, then the hydrogenation ratio is (P1-P2) / P1. Among them, the nitrile rubber and the hydrogenated nitrile rubber obtained after its hydrogenation have similar structural units, for example, the molar ratio of butadiene structural units (including hydrogenated and unhydrogenated) and acrylonitrile is consistent. By detecting the molar ratio of butadiene structural units (including hydrogenated and unhydrogenated) and acrylonitrile in hydrogenated nitrile rubber, the corresponding nitrile rubber raw material can be reversely deduced, and then the P1 value can be obtained.
[0041] Without limitation, the molar content of double bonds can be tested by the iodine value method: weigh a certain amount of the product to be tested, add chloroform to dissolve it, then add a certain amount of Wei's reagent (ICl) to allow the product to be tested to fully react with the Wei's reagent. After reaching the specified reaction time, add potassium iodide and water, and finally titrate with sodium thiosulfate until the yellow color almost disappears, then add starch solution, continue titrating and shake vigorously until the blue color just disappears, and the double bond content in the product to be tested can be calculated by titrating the amount of sodium thiosulfate used. The same sample is titrated twice according to the above test steps and the average value is taken.
[0042] Specifically, the hydrogenation ratio of the hydrogenated nitrile rubber includes, but is not limited to, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85% or a range between any two of the foregoing. Further, the hydrogenation ratio of the hydrogenated nitrile rubber is 55% to 70%.
[0043] In some embodiments, the weight average molecular weight of the hydrogenated nitrile rubber is 500 to 1000000. Reasonable control of the weight average molecular weight of the hydrogenated nitrile rubber can reduce the intermolecular forces and structural rigidity of the polymer while having a certain number of double bonds and cyano anchoring groups, which is conducive to its better dissolution and dispersion in the slurry, and can further improve the dispersion stability of the slurry, reduce the diaphragm resistance, and improve the first coulomb efficiency of the lithium-ion battery, while also being able to obtain a better high-temperature cycle capacity retention rate. Specifically, the weight average molecular weight of the hydrogenated nitrile rubber includes, but is not limited to, 500, 1000, 1500, 2000, 2500, 3000, 3500, 4000, 4500, 5000, 5500, 6000, 6500, 7000, 7500, 8000, 8500, 9000, 9500, 100000, 200000, 500000, 600000, 1000000 or a range between any two of the foregoing. Further, the weight average molecular weight is 1000 to 100000.
[0044] Without limitation, the weight average molecular weight of the hydrogenated nitrile rubber can be detected by the following method:
[0045] A Waters 2695 Isocratic HPLC gel chromatograph (differential refractive index detector 2141) was used. A polystyrene solution sample with a mass fraction of 3.0% was used as a reference, and a matching chromatographic column (oily: Styragel HT5 DMF7.8*300mm+Styragel HT4) was selected. A 3.0% polymer solution was prepared with purified N-methylpyrrolidone (NMP) solvent, and the prepared solution was allowed to stand for one day as a sample. During the test, tetrahydrofuran was first drawn with a syringe and rinsed, and repeated several times. Then 5 mL of the experimental solution was drawn, the air in the syringe was removed, and the needle tip was wiped dry. Finally, the sample solution was slowly injected into the injection port. After the indication was stable, the data was obtained to obtain the weight average molecular weight.
[0046] In some embodiments, the molar proportion of the acrylonitrile structural unit in the hydrogenated nitrile rubber is 5% to 30%. The cyano group in the acrylonitrile structural unit can be anchored with the positive electrode active material through coordination as an anchoring group, thereby improving the dispersion performance of the polymer. The molar proportion of the acrylonitrile structural unit in the hydrogenated nitrile rubber can be reasonably controlled, and while achieving a better anchoring effect, the hydrogenated nitrile rubber can retain a certain number of double bonds, thereby further improving the dispersion stability of the slurry, reducing the diaphragm resistance, and improving the first coulomb efficiency of the lithium-ion battery. At the same time, a better high-temperature cycle capacity retention rate can be obtained. Specifically, the molar proportion of the acrylonitrile structural unit in the hydrogenated nitrile rubber includes but is not limited to: 5%, 10%, 15%, 20%, 25%, 30% or a range between any two of the foregoing. Further, the molar proportion of the acrylonitrile structural unit is 10% to 20%.
[0047] Without limitation, the molar proportion of the acrylonitrile structural unit in the hydrogenated nitrile rubber can be converted into free cyano groups by burning, and then the cyano groups are titrated and determined.
[0048] Without limitation, the end groups of the hydrogenated nitrile rubber include one or more of hydroxyl, carboxyl, alkoxy, phenoxy, alkyl ester and aromatic ester groups.
[0049] It is understandable that the above-mentioned different types of hydrogenated nitrile rubber can be obtained from the market, or can be synthesized by purchasing corresponding monomers (all of which are commercially available) according to traditional methods. For example, the synthesis method of hydrogenated nitrile rubber generally includes the following steps:
[0050] (1) Copolymerizing butadiene and acrylonitrile to prepare an intermediate;
[0051]
[0052] (2) The intermediate is subjected to Pd / C catalytic hydrogenation to prepare hydrogenated nitrile rubber.
[0053]
[0054] In this step, hydrogenated nitrile rubbers with different weight average molecular weights, hydrogenation ratios or molar proportions of acrylonitrile structural units can be prepared by controlling the ratio of butadiene to acrylonitrile, reaction temperature, reaction time, hydrogenation pressure, etc.
[0055] In some embodiments, in the positive electrode active layer, the mass percentage of the hydrogenated nitrile rubber is 0.1% to 1%. Specifically, the mass percentage of the hydrogenated nitrile rubber includes but is not limited to: 0.1%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1% or a range between any two of the foregoing.
[0056] Without limitation, the positive electrode active layer can be dissolved by an organic solvent and the inorganic particles can be filtered out, and then separated using a thin layer chromatography column to obtain the amount of hydrogenated nitrile rubber, and then the mass percentage thereof in the positive electrode active layer can be calculated.
[0057] It is understandable that the lithium iron phosphate may include the lithium iron phosphate material itself, or may include a lithium iron phosphate product obtained by doping and / or coating the lithium iron phosphate material with trace elements. In some embodiments, the surface of the lithium iron phosphate has a carbon coating. The carbon coating on the surface of the lithium iron phosphate usually has residues such as -OH and -COOH, which can form hydrogen bonds with the cyanide groups in the hydrogenated nitrile rubber, thereby improving the dispersion effect of the slurry. Furthermore, the graphitization degree of the carbon coating is 10% to 30%. Reasonable control of the graphitization degree of the carbon coating can enhance the hydrogen bonding effect with the cyanide groups in the hydrogenated nitrile rubber, thereby enhancing the dispersion effect of the slurry.
[0058] Without limitation, the degree of graphitization of the carbon coating layer may be confirmed by the mass percentage of residual carbon after high-temperature calcination.
[0059] In some embodiments, the components of the positive electrode active layer further include a conductive agent.
[0060] In some embodiments, the conductive agent includes one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0061] In some embodiments, in the positive electrode active layer, the mass percentage of the conductive agent is 0.5% to 3%. Specifically, the mass percentage of the conductive agent includes but is not limited to: 0.5%, 1%, 1.5%, 2%, 2.5%, 3% or a range between any two of the foregoing.
[0062] Some other embodiments of the present application provide a positive electrode plate, the positive electrode plate includes a positive electrode active layer, the components of the positive electrode active layer include a positive electrode active material and an additive, the additive includes hydrogenated nitrile rubber, and the hydrogenation ratio of the hydrogenated nitrile rubber is 30% to 85%.
[0063] In some embodiments, the positive electrode plate is the positive electrode plate in the lithium ion battery as described above. It has similar solutions and advantages, which will not be repeated here.
[0064] Some other embodiments of the present application provide an electrical device, which includes at least one of the lithium-ion battery and the positive electrode sheet.
[0065] The lithium-ion battery and the electrical device of the present application will be described below with reference to the accompanying drawings as appropriate.
[0066] Generally, lithium-ion batteries include a positive electrode sheet, a negative electrode sheet, an electrolyte, and a separator. During the battery charging and discharging process, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is set between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.
[0067] The positive electrode plate includes a positive electrode current collector and a positive electrode active layer arranged on at least one surface of the positive electrode current collector. The positive electrode active layer is as described above and will not be described in detail here.
[0068] As a non-limiting example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode active layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.
[0069] In some embodiments, the positive electrode active layer may further include a binder. As non-limiting examples, the binder may include one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.
[0070] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material base layer. The composite current collector may be obtained by forming a metal material on a polymer material substrate. In the positive electrode current collector, non-limiting examples of the metal material may include one or more of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. In the positive electrode current collector, non-limiting examples of the polymer material substrate may include one or more of substrates such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.
[0071] In some of the embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder, the additive including hydrogenated nitrile rubber, and any other components are dispersed in a solvent to form a positive electrode slurry; the positive electrode slurry is coated on at least one side of the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained. The type of solvent can be selected from but not limited to any one of the aforementioned embodiments, such as N-methylpyrrolidone (NMP). The surface of the positive electrode collector coated with the positive electrode slurry can be on a single surface of the positive electrode collector or on both surfaces of the positive electrode collector. The surface of the positive electrode collector coated with the positive electrode slurry can be on a single surface of the positive electrode collector or on both surfaces of the positive electrode collector. The solid content of the positive electrode slurry can be 40wt%~80wt%. The viscosity of the positive electrode slurry at room temperature can be adjusted to 5000mPa·s~25000mPa·s. When applying the positive electrode slurry, the coating unit surface density based on dry weight (excluding solvent) can be 15 mg / cm 2 ~35mg / cm 2 The compaction density of the positive electrode can be 3.0g / cm 3 ~3.6g / cm 3 , optional 3.3g / cm 3 ~3.5g / cm 3 .
[0072] The negative electrode sheet includes a negative electrode current collector and a negative electrode active layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode active layer includes a negative electrode active material.
[0073] As a non-limiting example, the negative electrode current collector has two surfaces opposite to each other in its own thickness direction, and the negative electrode active layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.
[0074] In some of the embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be obtained by forming a metal material on a polymer material substrate. In the negative electrode current collector, non-limiting examples of the metal material may include one or more of copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. In the negative electrode current collector, non-limiting examples of the polymer material substrate may include one or more of substrates such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.
[0075] In some of the embodiments, the negative electrode active material may adopt the negative electrode active material for batteries known in the art. As a non-limiting example, the negative electrode active material may include one or more of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may include one or more of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may include one or more of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.
[0076] In some embodiments, the negative electrode active layer may further include a binder. The binder may include one or more of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).
[0077] In some embodiments, the negative electrode active layer may further include a conductive agent, which may include one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0078] In some of the embodiments, the negative electrode active layer may further include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).
[0079] In some of the embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (a non-limiting example of the solvent is deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on at least one side of the surface of the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained. The surface of the negative electrode collector coated with the negative electrode slurry can be on a single surface of the negative electrode collector or on both surfaces of the negative electrode collector. The solid content of the negative electrode slurry can be 40wt%~60wt%. The viscosity of the negative electrode slurry at room temperature can be adjusted to 2000mPa·s~10000mPa·s. When coating the negative electrode slurry, the coating unit surface density on a dry weight basis (excluding the solvent) can be 75g / m 2 ~220g / m 2 The compaction density of the negative electrode sheet can be 1.0g / cm 3 ~1.8g / cm 3 .
[0080] The electrolyte has the function of conducting ions between the positive electrode and the negative electrode. The present application has no particular restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.
[0081] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.
[0082] In some of the embodiments, the electrolyte salt may include one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bisfluorosulfonyl imide (LiFSI), lithium bistrifluoromethanesulfonyl imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorophosphate (LiPO2F2), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorobisoxalatophosphate (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP).
[0083] In some embodiments, the solvent may include ethylene carbonate (EC, ), propylene carbonate (PC, )、ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate ( ), fluoroethylene carbonate (FEC), methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.
[0084] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.
[0085] In some embodiments, the additive in the electrolyte may include, but is not limited to, one or more of fluoroethylene carbonate (FEC), difluoroethylene carbonate (DFEC), trifluoromethylethylene carbonate (TFPC), and the like.
[0086] In some embodiments, the lithium-ion battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.
[0087] In some embodiments, the material of the isolation membrane may include one or more of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane may be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer may be the same or different, without particular limitation.
[0088] In some embodiments, the isolation film has a thickness of 6 μm to 40 μm, and may be 12 μm to 20 μm.
[0089] In some of the embodiments, the positive electrode sheet, the negative electrode sheet and the separator can be formed into an electrode assembly by a winding process or a lamination process.
[0090] In some embodiments, the lithium-ion battery may include an outer packaging that can be used to encapsulate the electrode assembly and the electrolyte.
[0091] In some embodiments, the outer packaging of the lithium-ion battery may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the lithium-ion battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and further, non-limiting examples of plastic may include one or more of polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0092] A lithium-ion battery includes at least one battery cell. A lithium-ion battery may include one or more battery cells.
[0093] In this application, unless otherwise specified, "battery cell" refers to a basic unit that can realize the mutual conversion of chemical energy and electrical energy, and further, generally speaking, at least includes a positive electrode sheet, a negative electrode sheet and an electrolyte. During the battery charging and discharging process, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting active ions between the positive electrode sheet and the negative electrode sheet.
[0094] The present application has no particular limitation on the shape of the battery cell, which may be cylindrical, square or any other shape. Figure 1 A lithium-ion battery 1 having a square structure is used as an example.
[0095] In some of these embodiments, reference Figure 2, the outer packaging may include a shell 11 and a cover plate 13. Among them, the shell 11 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 11 has an opening connected to the receiving cavity, and the cover plate 13 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 12 through a winding process or a lamination process. The electrode assembly 12 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 12. The number of electrode assemblies 12 contained in the lithium-ion battery 1 can be one or more, and those skilled in the art can select according to actual needs.
[0096] The lithium-ion battery can be a battery module or a battery pack.
[0097] The battery module includes at least one battery cell. The number of battery cells contained in the battery module can be one or more, and those skilled in the art can select a suitable number according to the application and capacity of the battery module.
[0098] In the battery module, the plurality of battery cells may be arranged in sequence along the length direction of the battery module. Of course, they may also be arranged in any other manner. Further, the plurality of battery cells may be fixed by fasteners.
[0099] Optionally, the battery module may further include a housing having an accommodation space, and the plurality of battery cells are accommodated in the accommodation space.
[0100] In some of the embodiments, the battery modules may be assembled into a battery pack. The battery pack may contain one or more battery modules. Those skilled in the art may select a suitable number according to the application and capacity of the battery pack.
[0101] The battery pack may include a battery box and a plurality of battery modules disposed in the battery box. The battery box includes an upper box body and a lower box body, and the upper box body can be covered on the lower box body to form a closed space for accommodating the battery modules. The plurality of battery modules can be arranged in the battery box in any manner.
[0102] In addition, the present application also provides an electrical device, which includes the lithium-ion battery provided in the present application. The lithium-ion battery can be used as a power source for the electrical device, and can also be used as an energy storage unit for the electrical device. The electrical device may include mobile devices, electric vehicles, electric trains, ships and satellites, energy storage systems, etc., but are not limited to these. Among them, the mobile device may be, for example, a mobile phone, a laptop computer, etc.; the electric vehicle may be, for example, a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc., but are not limited to these.
[0103] As an electrical device, a lithium-ion battery can be selected according to its usage requirements.
[0104] As an example, the electric device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. In order to meet the electric device's requirements for high power and high energy density of lithium-ion batteries, a battery pack or a battery module may be used.
[0105] As another example, the electric device may be a mobile phone, a tablet computer, a notebook computer, etc. The electric device is usually required to be light and thin, and a battery cell may be used as a power source.
[0106] In order to make the technical problems, technical solutions and beneficial effects solved by the present application clearer, the present application will be further described in detail below in conjunction with the embodiments and drawings. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present application and its applications. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.
[0107] If no specific techniques or conditions are specified in the examples, the techniques or conditions described in the literature in the field or the product instructions are used. If no manufacturer is specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0108] The test methods involved in the embodiments are:
[0109] (1) Cathode slurry dispersion stability test:
[0110] The fluidity of the slurry is judged by visual inspection, and the viscosity change curve of the slurry is tested within 72 hours (sampling and testing every 8 hours). The stability of the positive electrode slurry is judged based on the fluidity and viscosity. When the slurry does not flow and the viscosity is extremely high, it is judged as severe gel. When the severe gel time is greater than 20 hours, the corresponding slurry dispersion stability can meet the production requirements of the battery.
[0111] (2) Diaphragm resistance (DCR) test:
[0112] Cut the dried positive electrode slurry (film layer) at the left, middle and right of the positive electrode sheet into small discs with a diameter of 3 mm. Turn on the power of Yuanneng Technology's electrode sheet resistor meter, place the "probe" of the electrode sheet resistor meter in a suitable position, click the "Start" button, and wait for the reading to stabilize before reading. Test two positions of each small disc, and finally calculate the average value of six measurements, which is the resistance of the electrode sheet film layer.
[0113] (3) First Coulomb efficiency:
[0114] At 25°C, the batteries of the above embodiments and comparative examples were charged at a constant current of 0.1C to a voltage of 3.65V. The charging capacity at this time was recorded as the first-cycle charging capacity of the lithium-ion battery. After that, they were allowed to stand for 5 minutes, and then discharged at a constant current of 0.1C to a voltage of 2.0V. The batteries were allowed to stand for 5 minutes. This was a charge and discharge cycle. The discharge capacity was recorded as the first-cycle discharge capacity of the lithium-ion battery, which was the initial capacity of the lithium-ion battery.
[0115] The first cycle coulombic efficiency (%) of a lithium-ion battery = first cycle discharge capacity / first cycle charge capacity × 100%.
[0116] (4) Cycle capacity retention rate:
[0117] At 45°C, the batteries in the examples and comparative examples were charged to 3.65V at a constant current of 1 / 3C, then charged to a current of 0.05C at a constant voltage of 3.65V, left for 10 minutes, and then discharged to 2.5V at 1 / 3C. The obtained capacity was recorded as the initial capacity C0. Repeat the above steps for the same battery, and record the discharge capacity C0 of the battery after the nth cycle. n , then the battery capacity retention rate after each cycle is:
[0118]
[0119] During the test, the first cycle corresponds to n=1, the second cycle corresponds to n=2, ... the 100th cycle corresponds to n=100. The battery capacity retention rate data corresponding to Example 1 in Table 1 is the data measured after 300 cycles under the above test conditions, that is, the value of P300.
[0120] Example 1
[0121] 1) Preparation of positive electrode
[0122] The positive electrode active material carbon-coated lithium iron phosphate (the graphitization degree of the carbon coating layer is 20%), conductive carbon black SP, binder PVDF and hydrogenated nitrile rubber (molecular weight is 1w, hydrogenation ratio is 70%, the molar ratio of acrylonitrile monomer structural unit is 15%, and the end groups on both sides are hydroxyl groups) are dispersed in the solvent NMP according to a weight ratio of 96.5:2:1:0.5 and mixed evenly to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on the double-sided surface of the positive electrode current collector aluminum foil, and after drying and cold pressing, a positive electrode sheet is obtained, wherein the coating amount per unit area on both sides is 0.7g / 1540.25mm 2 .
[0123] 2) Preparation of negative electrode sheet
[0124] The negative electrode active material artificial graphite, conductive agent carbon black (Super P), binder styrene-butadiene rubber (SBR) and sodium carboxymethyl cellulose (CMC) were mixed in a mass ratio of 96.4:0.7:1.8:1.1, and deionized water was added to obtain a negative electrode slurry under the action of a vacuum mixer; the negative electrode slurry was evenly coated on both sides of the copper foil; the copper foil was dried at room temperature and then transferred to a 120°C oven for drying for 1 hour, and then super-cold pressed and cut to obtain a negative electrode sheet, wherein the coating amount per unit area on both sides was 0.17 g / 1540.25 mm 2 .
[0125] 3) Isolation film
[0126] A 12μm thick polypropylene isolation film was selected.
[0127] 4) Preparation of electrolyte
[0128] The organic solvent is ethylene carbonate (EC) and ethyl methyl carbonate (EMC) mixed evenly in a volume ratio of 3:7. In an argon atmosphere glove box with a water content of <10ppm and O2 <0.1ppm, fully dried lithium salt LiPF6 is dissolved in the organic solvent and mixed evenly to obtain an electrolyte. The mass percentage of lithium salt is 12.5%.
[0129] 5) Preparation of batteries
[0130] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then wound into a square bare battery cell, loaded with an aluminum-plastic film, and then baked at 80°C to remove water, 10g of the corresponding non-aqueous electrolyte is injected, and the mouth is sealed. After standing, hot and cold pressing, formation, clamping, capacity division and other processes, a lithium-ion battery is obtained.
[0131] The lithium ion batteries provided in Examples 2 to 5 and Comparative Examples 1 to 2 are similar to those in Example 1, with the main difference being that hydrogenated nitrile rubbers with different hydrogenation ratios are used, as shown in Table 1 below.
[0132] Table 1
[0133]
[0134] The lithium ion batteries provided in Examples 6 to 10 are similar to those in Example 1, with the main difference being that hydrogenated nitrile rubbers with different weight average molecular weights are used, as shown in Table 2 below.
[0135] Table 2
[0136]
[0137] The lithium ion batteries provided in Examples 11 to 14 are similar to those in Example 1, with the main difference being that hydrogenated nitrile rubber with different molar proportions of acrylonitrile structural units is used, as shown in Table 3 below.
[0138] Table 3
[0139]
[0140] The solid content of the positive electrode slurry in each embodiment and comparative example is controlled at about 60%.
[0141] It can be seen from Tables 1 to 3 that, compared with Comparative Examples 1 to 2, Examples 1 to 17 can achieve better slurry dispersion stability by reasonably controlling the hydrogenation ratio of hydrogenated nitrile rubber to 30% to 85%, thereby obtaining lower diaphragm resistance, higher first coulomb efficiency, and higher cycle capacity retention rate. It can be seen from the comparison between Examples 1 to 5 that the hydrogenation ratio of hydrogenated nitrile rubber is further preferably 55% to 70%.
[0142] From the comparison between Example 1 and Examples 6 to 10, it can be seen that the reasonable control of the weight average molecular weight of the hydrogenated nitrile rubber can achieve better slurry dispersion stability, thereby obtaining lower diaphragm resistance, higher first coulomb efficiency, and higher cycle capacity retention rate.
[0143] From the comparison between Example 1 and Examples 11 to 14, it can be seen that the reasonable control of the molar ratio of the acrylonitrile structural unit of the hydrogenated nitrile rubber can achieve better slurry dispersion stability, thereby obtaining lower diaphragm resistance, higher first coulomb efficiency, and higher cycle capacity retention rate.
[0144] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0145] The above-mentioned embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent of the present application shall be subject to the attached claims.
Claims
1. A lithium-ion battery, comprising a positive electrode plate, characterized in that: The positive electrode plate includes a positive electrode active layer, the components of the positive electrode active layer include a positive electrode active material and an additive, the positive electrode active material includes lithium iron phosphate, the additive includes hydrogenated nitrile rubber, and the hydrogenation ratio of the hydrogenated nitrile rubber is 30% to 70%; The meaning of the hydrogenation ratio is: the molar content of double bonds in the nitrile rubber is P1, and the molar content of double bonds in the hydrogenated nitrile rubber obtained after the corresponding hydrogenation is P2, then the hydrogenation ratio is (P1-P2) / P1.
2. The lithium-ion battery according to claim 1, characterized in that The hydrogenation ratio of the hydrogenated nitrile rubber is 55% to 70%.
3. The lithium ion battery according to claim 1 or 2, characterized in that: The hydrogenated nitrile rubber has at least one of the following characteristics (1) to (2): (1) Weight average molecular weight is 500~1000000; (2) The molar proportion of acrylonitrile structural units is 5%~30%.
4. The lithium-ion battery according to claim 3, characterized in that: The hydrogenated nitrile rubber has at least one of the following characteristics (1) to (2): (1) Weight average molecular weight is 1000~100000; (2) The molar proportion of acrylonitrile structural units is 10%~20%.
5. The lithium ion battery according to any one of claims 1 to 2 and 4, characterized in that: In the positive electrode active layer, the mass percentage of the hydrogenated nitrile rubber is 0.1% to 1%.
6. The lithium ion battery according to any one of claims 1 to 2 and 4, characterized in that: The surface of the lithium iron phosphate has a carbon coating layer.
7. The lithium-ion battery according to claim 6, characterized in that: The graphitization degree of the carbon coating layer is 10% to 30%.
8. A positive electrode sheet, characterized in that: The positive electrode plate includes a positive electrode active layer, the components of the positive electrode active layer include a positive electrode active material and an additive, the additive includes hydrogenated nitrile rubber, and the hydrogenation ratio of the hydrogenated nitrile rubber is 30% to 70%; The meaning of the hydrogenation ratio is: the molar content of double bonds in the nitrile rubber is P1, and the molar content of double bonds in the hydrogenated nitrile rubber obtained after the corresponding hydrogenation is P2, then the hydrogenation ratio is (P1-P2) / P1.
9. The positive electrode sheet according to claim 8, characterized in that: The positive electrode sheet in the lithium ion battery according to any one of claims 2 to 7.
10. An electrical device, characterized in that: The invention comprises at least one of the lithium-ion battery according to any one of claims 1 to 7 and the positive electrode sheet according to any one of claims 8 to 9.
Citation Information
Patent Citations
Positive electrode active material composition, positive electrode sheet, secondary battery, battery module, battery pack, and electric device
CN117223130A
Composition for preparing positive electrode of secondary battery, and positive electrode for secondary battery and secondary battery prepared using the same
KR1020170111749A
Slurry for positive electrode films, positive electrode film, secondary battery and method for producing positive electrode film
WO2023189294A1